Adorable fruits & vegetables to crochet : delicious decorations for your table - Clesse, Marie (Dover Publications, Inc., 2020)
"A cute collection of 25 projects to create decorative crocheted fruit and vegetables, ranging from strawberries, kiwi, and oranges to pumpkin, cauliflower, even a halved avocado with the pit prominently sticking out. There's a banana complete with a peel that allows you to unpeel and remove the fruit, a full lemon and one that's halved, and a pea pod complete with little peas can be removed from the pod. This is a fun book for crafters at all skill levels, and each project includes a detailed stitch chart and accompanying photos"--